The Impact of Firm Performance on Annual Report Readability: Evidence from Listed Firms in Ghana - Shuibin Gu; Regina Naa Amua Dodoo (Universitas Hayam Wuruk Perbanas, 2019)
Annual report readability is necessary to prevent the imbalanced flow of information and enhance stakeholders’ view of the firm. For that reason, it is crucial to examine the factors than can affect it. This study attempts to find the impact of firm performance on annual report readability. The study consists of 15 listed firms on the Ghana Stock Exchange within the period 2008 to 2017. By applying the fixed and random effect method, the Hausman test was conducted to select a suitable method, the result based on the random effect method states that firm performance positively relates to annual report readability. In addition, the study finds out that corporate governance exerted a negative influence on the readability of the annual report. Finally, the study adopts F-MOLS to test Robustness which confirms the main result. This result implies that there are other determinants and factors that influence annual report readability rather than firms or managers manipulating financial reports to win investor sentiment.